Pemberdayaan Ekonomi Desa melalui Usaha Mikro, Kecil, dan Menengah (UMKM) Pertanian Berkelanjutan di Desa Kudadepa - Dede Rizal Nursamsi; Ai Rosita Nurkharisma; Wildan Arbi PB; Radisa Rosiana Nursyahbani; Muhamad Ansor; Fitri Yuliyani (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
This study aims to analyze efforts to empower the village economy through the development of Micro, Small, and Medium Enterprises (MSMEs) based on sustainable agriculture in Kudadepa Village, Sukahening District, Tasikmalaya Regency. The background of this study is the low added value of village agricultural products that have so far relied on traditional distribution systems, so that farmers tend to sell products to collectors at less profitable prices. The research method used is descriptive qualitative with a field study approach through observation, interviews, and documentation. Research participants included agricultural MSMEs, village officials, and local consumers. The results show that strengthening the capacity of MSMEs can be done through three main strategies: improving managerial and technical skills for business actors, product innovation based on organic and environmentally friendly agriculture, and developing a broader digital marketing network. In addition, support from the village government and related institutions plays a crucial role in providing access to capital, business mentoring, and facilitating ongoing training. The conclusion of this study confirms that the development of sustainable agricultural MSMEs not only increases community income but also encourages village economic independence and environmental sustainability. Thus, the MSME-based empowerment model can be an effective strategy in building an inclusive and competitive rural economy.